Determination Of Total Flavonoid Levels Of Ridge Gourd Fruit With Uv-Vis Spectrumfotometry Method - Indriani Estikawati; Novena Yety Lindawati (Universitas Muhammadiyah Magelang, 2019)
Ridge gourd fruit (Luffa acutangula (L.) Roxb.) is one kind of tuber plants that grows in many tropical and various kinds. Ridge gourd fruit are widely consumed by the people of Indonesia. Chemical content of ridge gourd fruit such as flavonoids has the potential as antidiabetic. The purpose of this study is to determine the total flavonoid levels found in ridge gourd fruit by uv-vis spectropotometric method. Ridge gourd fruit extracted with metanol:cloroform (4:1) mixture by maceration method. Analysis qualitative of flavonoid content were carried out with Wilstater, Smith Metacalfe, and Thin Layer Kromatgrafi (TLC). Quantitative analysis of total flavonoids using UV-Vis spectrophotometric method at wavelength 413,2 nm with complex forming reactions AlCl3. The results of qualitative tests show that ridge gourd fruit contain flavonoids positive. The average level of total flavonoids of ridge gourd fruit is 10,08 and the coeficient of variation (CV) with the result of 0,69%